The wild + free family : forging your own path to a life full of wonder, adventure, and connection - Arment, Ainsley (HarperOne, an imprint of HarperCollins Publishers, 2022)
"As parents, we dream of creating a magical childhood for our kids, yet it can be so easy to slip into autopilot. Ainsley Arment is no stranger to the barrage of decisions, opportunities, and daily tasks that each day brings. But what Ainsley has discovered is that the magic of life isn't found in the hustle and bustle of constant activity but in the intentional ordinary decisions of our days. And when we assume that a family has to look or act a certain way, we miss the opportunity to build a meaningful and fulfilling life together. Drawn from her family's stories and those shared by the Wild + Free community, The Wild + Free Family explores how to create a family culture that breaks the mold by seeking to connect with our children, unleash their gifts, pursue a shared vision together, and redeem generational brokenness, among so much more. Inside these pages are Ainsley's words of encouragement, honesty, and wisdom, guiding all parents to create a home where families can forge their own path to love stronger, live more fully, and grow closer to each other"--